Reinforced perovskite hollow fiber membranes with stainless steel as the reactive sintering aid for oxygen separation - Wang, B.; Song, J.; Tan, X.; Meng, B.; Liu, Jian; Liu, Shaomin (2016)
Unlike polymeric hollow fiber membrane which has been successfully used in industrial applications, ceramic hollow fiber membrane has not been widely applied due to their brittle nature of ceramic materials. In this work, La0.6Sr0.4CoO3−δ (LSC) hollow fiber membrane was fabricated for oxygen permeation using a combined phase inversion/sintering technique. As expected, the mechanical strength of LSC hollow fiber is very low, only 72.76 MPa from three-point-bending test. In order to improve the mechanical strength of perovskite hollow fibers, stainless steel powder was added in the perovskite for the starting membrane material. During high temperature sintering, the stainless steel phase was transferred to iron oxide phase. The mechanical strength of the resultant hollow fiber membranes has been significantly improved due to the enhanced densification by the melting stainless steel at high temperature which played a role as the sintering aid, and the volume expansion caused by the iron oxide formation from the metal phase. There is a balance between the enhanced mechanical strength and the lowered oxygen flux due to the addition of non-oxygen permeable material. Experimental results demonstrate that the optimal weight percentage of stainless steel powder mixed in the perovskite is 10%. Compared to the pristine membrane, the mechanical strength of the resultant composite membrane was improved by 80% although the flux was lowered by 18% relative to the original flux.